PENINGKATAN PEMAHAMAN SISWA TENTANG SISTEM PENCERNAAN MANUSIA MENGGUNAKAN MODEL PBL DENGAN MEDIA CHARTA - Widiasih; Sintia, Dina (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
Motivated by the low science score of grade VIII.5 students of SMP Negeri 1 Jejawi on the human digestive system material which slightly reached the KKM score, due to students' understanding of the human digestive system material is still very low. This is what encourages learning improvement by focusing on improving teacher performance in using the PBL learning model with charta media on the human digestive system material. Learning improvement aims to increase students' understanding of the material of the Human Digestive System. This research was conducted in grade VIII.5 of SMP Negeri 1 Jejawi, Ogan Komering Ilir regency in the odd semester of 2022. The method used in this study is Classroom Action Research which is divided into two cycles of learning improvement. The instruments taken are in the form of student evaluation results and observation sheets of student activities during learning. Analysis of the results of student learning evaluation of 28 grade VIII.5 students, namely the percentage of classical student completeness of 10.7% in the first cycle, and in the second cycle increased by 43%. Based on the results of both cycles, science evaluation scores for grade VIII.5 students of SMP Negeri 1 Jejawi were obtained, the material of the human digestive system has increased. To improve the grades of students who are not optimal, it is recommended to make improvements to the third cycle of learning.